Композиция для ингибирования асфальтосмолопарафиновых отложений - Прозорова И. В. Ирина Витальевна; Бондалетов В. Г. Владимир Григорьевич; Копытов М. А. Михаил Александрович; Лоскутова Ю. В. Юлия Владимировна; Приходько С. И. Сергей Иванович; Антонов И. Г. Игорь Герасимович; Юдина Н. В. Наталья Васильевна
опубл. 10.04.05